A set of vectors and strains for chromosomal integration in fission yeast - Akihisa Matsuyama; Atsushi Hashimoto; Shinichi Nishimura; Minoru Yoshida (Scientific Reports, 2023)
Abstract The expression of heterologous genes is an important technique in yeast genetics. In fission yeast, the leu1 and ura4 genes have been used mainly as selectable markers for heterologous expression. To expand the repertoire of selection markers available for heterologous expression of genes, here we developed new host-vector systems employing lys1 and arg3. By employing genome editing with the CRISPR/Cas9 system, we isolated several alleles of lys1 and arg3, each having a critical mutation in the ORF region. In parallel, we developed a set of vectors that complement the amino acid auxotrophy of lys1 and arg3 mutants when integrated into each locus. Using these vectors in combination with the previously developed integration vector pDUAL, we successfully observed the localization of three proteins in a cell simultaneously by fusing them with different fluorescent proteins. Thus, these vectors enable combinatorial expression of heterologous genes, which addresses increasingly diverse experimental challenges.